Continuous positive airway pressure to reduce the risk of early peripheral oxygen desaturation after onset of apnoea in children: A double-blind randomised controlled trial - dos Santos Neto, Jayme Marques; de Carvalho, Clístenes Cristian; de Andrade, Lívia Barboza; Dos Santos, Thiago Gadelha Batista; Andrade, Rebeca Gonelli Albanez da Cunha; Fernandes, Raphaella Amanda Maria Leite; de Orange, Flavia Augusta (PLOS ONE, 2021)
Continuous positive airway pressure (CPAP) during anaesthesia induction improves oxygen saturation (SpO2) outcomes in adults subjected to airway manipulation, and could similarly support oxygenation in children. We evaluated whether CPAP ventilation and passive CPAP oxygenation in children would defer a SpO2 decrease to 95% after apnoea onset compared to the regular technique in which no positive airway pressure is applied. In this double-blind, parallel, randomised controlled clinical trial, 68 children aged 2–6 years with ASA I–II who underwent surgery under general anaesthesia were divided into CPAP and control groups (n = 34 in each group). The intervention was CPAP ventilation and passive CPAP oxygenation using an anaesthesia workstation. The primary outcome was the elapsed time until SpO2 decreased to 95% during a follow-up period of 300 s from apnoea onset (T1). We also recorded the time required to regain baseline levels from an SpO2 of 95% aided by positive pressure ventilation (T2). The median T1 was 278 s (95% confidence interval [CI]: 188–368) in the CPAP group and 124 s (95% CI: 92–157) in the control group (median difference: 154 s; 95% CI: 58–249; p = 0.002). There were 17 (50%) and 32 (94.1%) primary events in the CPAP and control groups, respectively. The hazard ratio was 0.26 (95% CI: 0.14–0.48; p<0.001). The median for T2 was 21 s (95% CI: 13–29) and 29 s (95% CI: 22–36) in the CPAP and control groups, respectively (median difference: 8 s; 95% CI: -3 to 19; p = 0.142). SpO2 was significantly higher in the CPAP group than in the control group throughout the consecutive measures between 60 and 210 s (with p ranging from 0.047 to <0.001). Thus, in the age groups examined, CPAP ventilation and passive CPAP oxygenation deferred SpO2 decrease after apnoea onset compared to the regular technique with no positive airway pressure.